Effects of a non-standard information leaflet on patient recruitment in acute care: Embedded cluster-randomised controlled trial - Carolin Höckelmann; Marcelina Roos; Wiebke Müller; Martin N. Dichter; Sascha Köpke (PLoS ONE, 2025)
Background Recruiting study participants is a key component and major challenge in clinical research. Evidence shows that the design of written study information can influence recruitment success. However, there is a lack of research on the effectiveness and acceptability of different written study information. Objective We aimed to investigate the effectiveness and acceptability of an information leaflet including an information video compared to a formal information letter in patient recruitment in acute care. Design We conducted a cluster-randomised controlled trial embedded in a cross-sectional study (“Sleep Acute host study”) addressing patients’ sleep in hospitals. Methods In a stratified random sample of hospitals, we allocated selected wards either to the intervention group (information leaflet including a link to an information video) or the control group (formal information letter) using external concealed randomisation. Adult patients hospitalised for at least 48 hours were eligible for participation. Our primary endpoint was recruitment success measured by the participation rate in the Sleep Acute host study. The secondary endpoint was acceptability of the written study information. Persons involved in the analyses were blinded concerning group allocation. Results In total, 53 wards with 498 patients were cluster-randomised, 28 wards with 262 patients were allocated to the intervention group and 25 wards with 236 patients to the control group. The participation rate in the Sleep Acute host study was 51.1% (134 of 262) for the intervention and 47.5% (112 of 236) for the control group (OR 1.186 (0.698 to 2.013), p = 0.528). There were no significant differences concerning the acceptability of the written study information between both groups. Conclusions More patients who received an information leaflet including a link to an information video participated in the host study, although the difference is not statistically significant. Study registration DRKS-ID: DRKS00029707. Registered on 30. August 2022